From toxic materials to food-grade materials: A major challenge for battery design – A mini review - Le Borgne, Marina; Ximenes, Perrine; Le Borgne, Marc (De Remediis, 2025)
The use of batteries, found in telephones, remote controls, and medical devices, is an integral part of our daily lives. Unfortunately, the routine use of these electronic devices has harmful effects on the environment, primarily due to the pollution generated by heavy metals. This article traces the history of batteries, starting with the birth of the voltaic battery in 1799, invented by Alessandro Volta. This discovery, based on the principle of redox reactions between zinc and copper, was subsequently taken up and improved on numerous times. In 1836, John Frederic Daniell designed a two-compartment cell, stabilized by depolarizers and connected by a salt bridge. To meet today's climate challenges, researchers continue to design batteries, but this time they are biodegradable, edible, rechargeable, and therefore sustainable. In recent years, we have seen the emergence of highly innovative concepts. Some scientists, for example, are using cuttlefish ink to extract melanin. In a sodium-ion battery, this molecule acts as a natural anode, enabling sodium ions to be stored and thus contributing to the device's eco-friendliness. Other innovative research has also emerged, using other natural ingredients such as quercetin and riboflavin. These technological advances are of particular interest to the healthcare sector for the development of implantable medical devices.